The umbrella - Ferry, Beth; Lichtenheld, Tom (New York, NY : Clarion Books, 2023)
A little girl and her dog find unexpected ways to spread the light in their dreary town where it always rains, showing that happiness is contagious.
Publishers Weekly, January 2023
Kirkus Review, December 2022
1.3
K-3
Keywords: Rain and rainfall -- Juvenile fiction; Umbrellas -- Juvenile fiction; Happiness -- Juvenile fiction; Rain and rainfall -- Fiction; Umbrellas -- Fiction; Happiness -- Fiction; Stories in rhyme; Dogs -- Juvenile fiction; City and town life -- Juvenile fiction